Djibouti : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
This Poverty Reduction Strategy Paper (PRSP) on Djibouti explains past strategies and the PRSP formulation process. Djibouti suffers from a gross lack of reliable health statistics. Available information gives only a fragmented picture of the reality, but globally, it reveals a difficult health situation. The promotion of a coherent and integrated employment policy must be one of the cornerstones of the poverty reduction strategy. Being a new country with few human resources, Djibouti's governance problems considerably limit the effectiveness of government economic and social programs for the poor.